Rigid Dynamic Model and Analysis of 5-DOF Parallel Mechanism. (30th July 2015) - Chen, Xiulong; Liang, Xiaoxia; Deng, Yu; Wang, Qing
This paper introduces a novel 4-UPS-RPS spatial parallel mechanism, which can achieve three rotation degrees and two translation degrees of freedom. A rigid dynamic model is established and analysis of the parallel mechanism is carried out. The kinematics of the RPS and UPS driving limbs are analysed and the velocity-mapping relationships between the driving limbs and the other parts are built. The load conditions of the parts are analysed, and the rigid dynamic model of the 4-UPS-RPS parallel mechanism is derived by the virtual work principle approach. Using the example of the parallel mechanism movement, a driving forces analysis of the 4-UPS-RPS parallel mechanism is carried out, and the correctness of the rigid dynamic model is verified by numerical calculation and virtual simulation.